Enzymology of activated sewage sludge during anaerobic treatment of wastewaters : identification, characterisation, isolation and partial purification of proteases - Tshivhunge, Azwiedziswi Sylvia (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2001)
During anaerobic digestion bacteria inside the digester require a carbon source for their growth and metabolism, sewage sludge was used as a carbon source in this study. The COD content was used to measure the disappearance of the substrate. COD content was reduced by 48.3% and 49% in the methanogenic and sulphidogenic bioreactors, respectively, while sulphate concentration was reduced by 40%, producing 70mg/L of hydrogen sulphide as the end product over the first 5-7 days. Sulphate (which is used as a terminal electron acceptor of sulphur reducing bacteria) has little or no effect on the sulphidogenic and methanogenic proteases. Sulphite and sulphide (the intermediate and end product of sulphate reduction) increased protease activity by 20% and 40%-80%, respectively. Maximum protease activity occurred on day 21 in the methanogenic reactor and on day 9 in the sulphidogenic reactor. The absorbance, which indicates the level of amino acid increased to 2 and 9 for methanogenic and sulphidogenic bioreactors, respectively. Proteases that were active during anaerobic digestion were associated with the pellet (organic particulate matter) of the sewage. These enzymes have an optimum activity at pH 10 and at temperature of 50°C. The proteases that were active at pH 5 and 7, had optimum temperatures at 30°C and 60°C, respectively. Due to their association with organic particulate matter, these enzymes were stable at their optimum temperatures for at least five hours at their respective pH. Inhibition by PMSF, TPCK and 1.10-phenanthroline suggested that proteases inside the anaerobic digester are a mixture of cysteine, serine and metalloproteases. At pH 5, however, EDTA appeared to enhance protease activity by 368% (three-fold). Acetic acid decreased protease activity by 21%, while both propionic and butyric acid at 200 mg/L cause total inhibition of protease activity while these acids at higher pH (where they exist as their corresponding salts) exerted little effect. Copper, iron and zinc inhibited protease activity by 85% at pH 5 with concentrations ranging between 200 and 600 mg/L. On the other hand, nickel, showed an increase in protease activity of nearly 250%. At pH 7 and 10, copper had no effect on protease activity while iron, nickel and zinc inhibited these enzymes by 20-40%. Proteases at pH 7 were extracted from the pellet by sonication, releasing 50% of the total enzymes into the solution. The enzymes were precipitated by ammonium sulphate precipitation, and further purified by ion exchange chromatography and gel filtration. Ion exchange chromatography revealed that most of the enzymes that hydrolyse proteins are negatively charged while gel filtration showed that their molecular weight is approximately 500 kDa.
Keywords: Sewage sludge; Sewage sludge -- Environmental aspects; Sewage sludge digestion; Anaerobic bacteria